2005
DOI: 10.1590/s0074-02762005000900033
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil transepithelial migration: role of toll-like receptors in mucosal inflammation

Abstract: The symptomatic phases of many inflammatory diseases are characterized by migration of large numbers of neutrophils (PMN)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 84 publications
1
26
0
3
Order By: Relevance
“…At a higher magnification, the upregulation in TLR4 expression was observed to be localized primarily within the cytoplasm of oral epithelial cells ( Figure 3E). This is in accordance with previous studies showing that TLR4 is generally localized to the Golgi apparatus of intestinal epithelial cells (2,27) and indicates that responsiveness of the epithelium may involve some sort of cellular processing and transport (14). Immunoelectron microscopy revealed TLR4 expression on the cell surface at the site of direct host-pathogen contact ( Epithelial TLR4 protects the oral mucosa from fungal invasion and cell injury.…”
Section: Tlr Gene Expression In Oral Rhe Is Representative Of the Orasupporting
confidence: 92%
See 2 more Smart Citations
“…At a higher magnification, the upregulation in TLR4 expression was observed to be localized primarily within the cytoplasm of oral epithelial cells ( Figure 3E). This is in accordance with previous studies showing that TLR4 is generally localized to the Golgi apparatus of intestinal epithelial cells (2,27) and indicates that responsiveness of the epithelium may involve some sort of cellular processing and transport (14). Immunoelectron microscopy revealed TLR4 expression on the cell surface at the site of direct host-pathogen contact ( Epithelial TLR4 protects the oral mucosa from fungal invasion and cell injury.…”
Section: Tlr Gene Expression In Oral Rhe Is Representative Of the Orasupporting
confidence: 92%
“…IL-8 and GM-CSF are key cytokines in recruiting and stimulating PMNs to sites of microbial infection (1,4,14), which are rapidly activated by exposure to proinflammatory cytokines including IL-1α, IL-1β, IL-6, and TNF-α (28). Together with the observation that epithelial macrophage inflammatory protein-1β (MIP-1β) and monocyte chemoattractant protein-1 (MCP-1) production was also increased after PMN supplementation of the C. albicansinfected oral RHE model, we investigated whether blocking of these 8 cytokines with neutralizing antibodies could prevent epithelial TLR4 upregulation and subsequent protection.…”
Section: Knockdown Of Epithelial Tlr4 By Rna Interference Restores Fumentioning
confidence: 99%
See 1 more Smart Citation
“…Transepithelial migration of neutrophils from the intravascular compartment to the sites of inflammation is a regulated multistep process involving a series of coordinated interactions between adhesion molecules expressed on the surface of endothelial cells and their counterparts on leukocytes [78][79][80][81][82][83]. ZHENG et al [85] have reported that serum levels of E-selectin, ICAM-1 and VCAM-1 were significantly higher in bronchiectasis with regard to control subjects.…”
Section: The Role Of Cells In Bronchiectasis Airway Inflammation Neutmentioning
confidence: 99%
“…Paneth cells distal of the left colon flexure (Bentley et al, 2002) none few some many Lymphocytes (Ajioka et al, 2005;Bentley et al, 2002;Eksteen et al, 2008) normal concentration minor increase relevant increase severe increase Plasma cells (Bentley et al, 2002;Morson, 1971) normal concentration minor increase relevant increase severe increase Eosinophils (Eksteen et al, 2008;SchmitzMoormann & Himmelmann, 1988) normal concentration minor increase relevant increase severe increase unspecific inflammatory infiltrates (Bentley et al, 2002) none minor moderate severe PMNs in Lamina propria and Lamina epithelialis (Glickman et al, 2004;Reaves et al, 2005;Wang et al, 2004) normal concentration minor increase relevant increase severe increase Crypt abscesses (Bentley et al, 2002;Glickman et al, 2004;Hendrickson et al, 2002;Morson, 1971) To publish a book on colonoscopy suitable for an international medical audience, drawing upon the expertise and talents of many outstanding world-wide clinicians, is a daunting task. New developments in videocolonoscope instruments, procedural technique, patient selection and preparation, and moderate sedation and monitoring are being made and reported daily in both the medical and the lay press.…”
mentioning
confidence: 99%